Stimulating Constructive and Destructive Leadership Behaviours through the Emperor of Lanka and Villain of Ramayana - Shyam B. R.; Aithal P. S. (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: All are kings. But some follow rules and some break rules. The question is why? Ram and Krishna act for the benefit of others, the larger group. Ravan and Duryodhan are more interested in their glory even if their respective kingdoms are destroyed. On a parallel track, it constantly distinguishes Durga, the symbol of social status, from Shakti, the inner power - physical and mental prowess. On exemplifying positive and negative leadership through Ram, Ravan, Krishna and Duryodhan. The journey towards leadership is a journey from ‘me’ to ‘we’. Thus, linking mythological themes & management with the present-day materialistic world is not easy. The present research links and contextualizes the concepts of virtue & vice leadership behaviours and personality types through the king of Lanka to business and management with the ancient Indian texts. Objectives: The researchers have set the following primary objectives and the current study investigates 2 broad research questions: (1) To evaluate Ramayan’s character Ravan stimulates constructive and destructive leadership behaviours. (2) To identify the personality type (MBTI) of the Anti-Hero, Ravana. Design/Methodology/Approach: The study is based on both secondary & primary evidence. Hypotheses are stated for the various variables selected and analyzed to prove or disprove the same without any errors. Findings/Result: There were stimulating virtue and vice leadership behaviours through the emperor of Lanka and the villain of Ramayana. Also, there was a personality type (MBTI) of Anti-Hero, Ravana to business and management with the ancient Indian texts. Research Limitations/Implications: In the present research an attempt is made by the researchers to understand the research gap in the area hence a conceptual idea is proposed and the research goes further to advance significance to discover the degree of relationship to evaluate Ramayan character Ravan stimulates behaviours showing high moral standards (constructive leadership behaviours ) & bad behaviours (destructive leadership behaviours) & to identify personality type (MBTI) of Anti-Hero, Ravana. Originality/New Knowledge/Interpretation/Value: Many of the earlier studies have proved that, Indian mythology has a deeper meaning than basic good and evil. There is an intriguing narrative at every turn, if one is willing to go deep. Ravana portrayed a villain, but it’s crucial to understand why he chose to do so. Actually, the goal was to balance the forces of good and evil. It is understandable why he is still revered in some areas of the world. Ravana is often looked down upon as an evil character in the Ramayana. But nobody can be really classified as completely black or white. Like every other mortal, Ravana also had shades of grey. But none of us can ever deny the fact that he was the most dexterous character in the epic as well. Hence, this study helps in concluding that, a comparative look at virtue and vice leadership behaviours and personality type makes Ravana the most interesting Ramayana character ever and offers insight into business and management with the ancient Indian texts. Paper Type: The study is based on both secondary & primary evidence.